Trace metals, peroxidase activity, PAHs contents and ecophysiological changes in Quercus ilex leaves in the urban area of Caserta (Italy). - Papa, S; Bartoli, G; Nacca, F; D'Abrosca, B; Cembrola, E; Pellegrino, a; Fiorentino, a; Fuggi, A; Fioretto, a (Journal of environmental management, 2012)
Trace metals and polycyclic aromatic hydrocarbons, severely affecting human, animal and plants health, highly contribute to the air pollution in urban areas mainly due to car traffic. In this study the air biomonitoring of the city of Caserta (South Italy) has been performed by using Quercus ilex L., a widespread ornamental plant in parks, gardens and avenues. The plant leaves from different sites within the urban area were collected and used to determine the concentrations of V, Cd, Cr, Pb, Ni, Cu, and PAHs as well as the free amino acid content and peroxidase enzyme activity as indices of the leaf physiological conditions. All the tested trace metals showed concentrations higher than the control site. Lead was positively correlated to Cd and Cr and showed, also, a positive trend with Ni and Cu that, in their turn, were highly correlated between them. Positive and significant correlations were evidenced between total PAHs and carcinogenic PAHs and negative correlations between those and all trace metals assayed except V. Cu and Cd contents evidence negative correlations with peroxidase activity, and the free amino acid contents. The PAHs, in particular Carc-PAHs, were negatively correlated to the tested heavy metals. POD was positively correlated only with V and negatively correlated with Cu and Cd.
Keywords: Amino acid contents; PAHs; peroxidase; Quercus ilex leaves; Trace Elements; Urban area

Laccase and peroxidase isoenzymes during leaf litter decomposition of Quercus ilex in a Mediterranean ecosystem - Di Nardo, C.; Cinquegrana, A.; Papa, S.; Fuggi, A.; Fioretto, A. (Soil Biology and Biochemistry, 2004)
The dynamics of leaf litter decomposition of Quercus ilex (L.) were investigated over a 2 year period by determining the activities and isoenzyme distribution of laccases and peroxidases. The analysis of isoenzymes was performed by isoelectric focusing on high stability pH gradients with high resolving power. The preparation of zymograms was carried out using the leaf litter extract without previous concentration. During litter decomposition, laccase and peroxidase activities changed as well as the type and number of enzyme isoforms. The activities of both enzymes were low (%0.017 and %0.031 mmol o-tolidine oxidized hK1 gK1 d.w. for laccase and peroxidase, respectively) in ﬁrst year and increased in October–January of the second year of litter decay. The highest activities measured after 15–18 months of litter exposure (0.37G0.03 and 0.19G0.02 mmol o-tolidine oxidized hK1 gK1 d.w. for laccase and peroxidase, respectively), showed that litter chemical composition affected the growth of ligninolytic microbial community. The activation energy for laccase and peroxidase reactions also changed during decomposition: the highest values (55G6 kJ molK1 for laccase and 60G6 kJ molK1 for peroxidase) occurred in autumn–winter, even if spatial changes were evidenced. Some enzyme isoforms (pIZ5.3 and 5.5 for laccase and pIZ5.0 and 5.1 for peroxidase, respectively), contributed more than others to the overall laccase and peroxidase activity, suggesting that some ligninolytic species bloomed in particular seasons of the year, even if other species with similar functional activities colonized the litter.
Keywords: Enzyme activity; isoelectrofocusing; laccase; litter decomposition; peroxidase

Laccase and peroxidase isoenzymes during leaf litter decomposition of Quercus ilex in a Mediterranean ecosystem - Di Nardo, C; Cinquegrana, A; Papa, S; Fuggi, A; Fioretto, a (Soil Biology and Biochemistry, 2004)
The dynamics of leaf litter decomposition of Quercus ilex (L.) were investigated over a 2 year period by determining the activities and isoenzyme distribution of laccases and peroxidases. The analysis of isoenzymes was performed by isoelectric focusing on high stability pH gradients with high resolving power. The preparation of zymograms was carried out using the leaf litter extract without previous concentration. During litter decomposition, laccase and peroxidase activities changed as well as the type and number of enzyme isoforms. The activities of both enzymes were low (%0.017 and %0.031 mmol o-tolidine oxidized hK1 gK1 d.w. for laccase and peroxidase, respectively) in ﬁrst year and increased in October–January of the second year of litter decay. The highest activities measured after 15–18 months of litter exposure (0.37G0.03 and 0.19G0.02 mmol o-tolidine oxidized hK1 gK1 d.w. for laccase and peroxidase, respectively), showed that litter chemical composition affected the growth of ligninolytic microbial community. The activation energy for laccase and peroxidase reactions also changed during decomposition: the highest values (55G6 kJ molK1 for laccase and 60G6 kJ molK1 for peroxidase) occurred in autumn–winter, even if spatial changes were evidenced. Some enzyme isoforms (pIZ5.3 and 5.5 for laccase and pIZ5.0 and 5.1 for peroxidase, respectively), contributed more than others to the overall laccase and peroxidase activity, suggesting that some ligninolytic species bloomed in particular seasons of the year, even if other species with similar functional activities colonized the litter.
Keywords: Enzyme activity; isoelectrofocusing; laccase; litter decomposition; peroxidase

Annual variations of phenoloxidase activities in an evergreen oak litter: influence of certain biotic and abiotic factors - Criquet, S.; Farnet, A. M.; Tagger, S.; Petit, J. Le (Soil Biology and Biochemistry, 2000)
This study concerns ligninolysis phenomena occurring over 13 months in forest litter. Evergreen oak (Quercus ilex L.) litter was taken as a model because Quercus ilex L. is the most abundant tree species in forests of the French Mediterranean area. Several biotic and abiotic factors potentially involved in transformations of polyphenolic compounds, were measured between October 1997 and October 1998. These factors were: global fungal micro¯ora, the fungi producing phenoloxidases (PO+ ), the activities of several phenoloxidases, hydrosoluble phenols, and temperature, humidity and pH of the litter. Results showed that the annual dynamics of fungi and phenoloxidase activities appear to be seasonal, i.e. that these biotic factors such as, were optimal in autumn. A multiple regression analysis showed that there was no correlation between biotic factors such as, fungal populations and phenoloxidase activity and abiotic factors such as, temperature, humidity and pH. Laccases were the preponderant phenoloxidase activities during the year, while those of Mn-peroxidases only appeared in the autumn of 1997. Other phenoloxidases, lignin-peroxidases and tyrosinases were never detected. Interactions between laccases and humic substances were also investigated. Adsorption of laccases on humic substances leads to a shift in the optimal temperature activity of these enzymes from 50 to 308C. Activities of laccases also shifted towards more acidic values when laccases were not adsorbed on humic substances. Nevertheless, the optimal pH was the same (5.7) whether laccases were adsorbed or not to humic substances. Electrophoresis analysis showed little variations in the number of phenoloxidase isoenzymes. Indeed, laccases showed three isoenzymes during the year (Rf 0.23, 0.34 and 0.43). Only one isoform of Mn-peroxidase, with an Rf 0.21, was detected in the litter
Keywords: fungi; humic substances; laccase; litter; peroxidase

Annual variations of phenoloxidase activities in an evergreen oak litter: influence of certain biotic and abiotic factors - Criquet, S; Farnet, A M; Tagger, S; Petit, J Le (Soil Biology and Biochemistry, 2000)
This study concerns ligninolysis phenomena occurring over 13 months in forest litter. Evergreen oak (Quercus ilex L.) litter was taken as a model because Quercus ilex L. is the most abundant tree species in forests of the French Mediterranean area. Several biotic and abiotic factors potentially involved in transformations of polyphenolic compounds, were measured between October 1997 and October 1998. These factors were: global fungal micro¯ora, the fungi producing phenoloxidases (PO+ ), the activities of several phenoloxidases, hydrosoluble phenols, and temperature, humidity and pH of the litter. Results showed that the annual dynamics of fungi and phenoloxidase activities appear to be seasonal, i.e. that these biotic factors such as, were optimal in autumn. A multiple regression analysis showed that there was no correlation between biotic factors such as, fungal populations and phenoloxidase activity and abiotic factors such as, temperature, humidity and pH. Laccases were the preponderant phenoloxidase activities during the year, while those of Mn-peroxidases only appeared in the autumn of 1997. Other phenoloxidases, lignin-peroxidases and tyrosinases were never detected. Interactions between laccases and humic substances were also investigated. Adsorption of laccases on humic substances leads to a shift in the optimal temperature activity of these enzymes from 50 to 308C. Activities of laccases also shifted towards more acidic values when laccases were not adsorbed on humic substances. Nevertheless, the optimal pH was the same (5.7) whether laccases were adsorbed or not to humic substances. Electrophoresis analysis showed little variations in the number of phenoloxidase isoenzymes. Indeed, laccases showed three isoenzymes during the year (Rf 0.23, 0.34 and 0.43). Only one isoform of Mn-peroxidase, with an Rf 0.21, was detected in the litter
Keywords: fungi; humic substances; laccase; litter; peroxidase

Hydrogen Peroxide Production is a General Property of the Lignifying Xylem from Vascular Plants - BARCELÓ, A R O S (Annals of Botany, 1998)
Production of hydrogen peroxide (H2O2) by the lignifying xylem of several vascular plants has been studied using a new histochemical method based on the H2O2-dependent oxidation of 3,5,3′5′-tetramethylbenzidine (TMB) catalysed by cell wall peroxidases. This method allows H2O2to be determined in the range of 5–100 μm, where other methods, such as the KI/starch reagent, fail. With this method, it has been possible to determine H2O2production in the lignifying xylem of a wide range of vascular plants (gymnosperms and angiosperms). The capability of xylem tissues of sustaining H2O2production lends support to the hypothesis that cinnamyl alcohol polymerization in xylem vessels is caused by an H2O2-dependent oxidative coupling process.Copyright 1998 Annals of Botany Company
10.1006/anbo.1998.0655
Keywords: H2O2 generation; lignification; peroxidase; tetramethylbenzidine; Xylem

Hydrogen Peroxide Production is a General Property of the Lignifying Xylem from Vascular Plants - BARCELÓ, A. R. O. S. (Annals of Botany, 1998)
Production of hydrogen peroxide (H2O2) by the lignifying xylem of several vascular plants has been studied using a new histochemical method based on the H2O2-dependent oxidation of 3,5,3′5′-tetramethylbenzidine (TMB) catalysed by cell wall peroxidases. This method allows H2O2to be determined in the range of 5–100 μm, where other methods, such as the KI/starch reagent, fail. With this method, it has been possible to determine H2O2production in the lignifying xylem of a wide range of vascular plants (gymnosperms and angiosperms). The capability of xylem tissues of sustaining H2O2production lends support to the hypothesis that cinnamyl alcohol polymerization in xylem vessels is caused by an H2O2-dependent oxidative coupling process.Copyright 1998 Annals of Botany Company
10.1006/anbo.1998.065510.1006/anbo.1998.0655
Keywords: H2O2 generation; lignification; peroxidase; tetramethylbenzidine; Xylem